2018
DOI: 10.1080/14670100.2018.1460024
|View full text |Cite
|
Sign up to set email alerts
|

Real-time intracochlear imaging of automated cochlear implant insertions in whole decalcified cadaver cochleas using ultrasound

Abstract: This technique may be very useful for some studies, although the confounding effects of bone decalcification may make results of other studies too difficult to generalize. The approach could be adapted to other real-time imaging modalities, such as optical coherence tomography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Thus, a system which can predict ST volume is particularly valuable. In this study, the quasi-linear positive correlation between ST volume and A-and B-values enabled creation of a predictive algorithm to facilitate pre-operative prediction of ST indicated that higher insertion speed was associated with higher insertion forces (17,18). Our findings were reflected in a study recently published by Aebischer et al (19).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Thus, a system which can predict ST volume is particularly valuable. In this study, the quasi-linear positive correlation between ST volume and A-and B-values enabled creation of a predictive algorithm to facilitate pre-operative prediction of ST indicated that higher insertion speed was associated with higher insertion forces (17,18). Our findings were reflected in a study recently published by Aebischer et al (19).…”
Section: Discussionsupporting
confidence: 64%
“…The other assumption is that with larger ST volume, the helicotrema would also be larger allowing the cochlear fluid to escape from the ST to the scala vestibuli. Earlier reports by Kontorinis et al and Landry et al indicated that higher insertion speed was associated with higher insertion forces ( 17 , 18 ). Our findings were reflected in a study recently published by Aebischer et al ( 19 ).…”
Section: Discussionmentioning
confidence: 87%
“…The potentially easy and cost-effective implementation of HFUS during surgery to ensure damage-free visualization of the inner ear ultrastructure (23) makes it a promising imaging modality for the improvement of CI techniques. Intraoperative visibility of CI electrodes, using US imaging (24), could help detect a misplaced device, thus avoiding reoperation. Landry et al have demonstrated the feasibility of combining HFUS, automated CI insertion, and force sensing to monitor CI insertion dynamics in decalcified cadaver cochlea (24).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in case of an error in the reconstruction of either the orientations or the interdistances between the wires, the reconstruction procedure would worsen the line segment fitting, which would then impact the model matching and finally result in a degraded accuracy value. Consequently, the metric defined in (14) enables to quantify to what extent the reconstruction procedure allows to preserve both the orientations and distance, which holds true for any structure.…”
Section: Evaluation Of System Performancesmentioning
confidence: 99%
“…Although also limited in depth, ultrasound (US) imaging allows to image further than OCT and was even shown to evaluate the functionality of the ossicles through the eardrum [11]. Besides, depending on the applied frequency, US imaging is capable to achieve sufficient spatial resolution to visualize anatomical landmarks of the ear that range from the ossicular chain [11], [12] to cochlear structures such as the basilar membrane [13], [14]. Combined with the low-cost, ease of use and safety of the corresponding imaging systems, these features make US an appropriate modality for initial contact with the patient.…”
Section: Introductionmentioning
confidence: 99%